Revival of dermatoglyphics: Syndromes and disorders, a review - N Lakshmana; Abhishek Singh Nayyar; B Vamsi Pavani; M V R Ratnam; G Upendra (Advances in Human Biology, 2017)
Dermatoglyphics deals with the study of the epidermal ridges and their configurations on the fingers, palms and soles. The word dermatoglyphics is derived from the Greek word 'Derma' meaning skin and 'glyphics' meaning carvings. Dermatoglyphics, once matured, remain unchanged throughout the life of an individual and are not influenced by either the environmental or, age-related factors. Because of these amazing qualities, these dermal ridges play a very crucial and important role in the personal identification of an individual, for forensic purposes, in twin diagnosis, racial variation and have applied values in various diseases and syndromes. Dermatoglyphics has, therefore, been accepted as a simple and inexpensive method for deciding whether a patient would have a particular genetic or, chromosomal defect or, not, and if so, to adopt the preventive strategies at the early enough stages.